Impulsivity and Difficulties in Emotional Regulation as Predictors of Binge-Watching Behaviours - Starosta, Jolanta; Izydorczyk, Bernadetta; Sitnik-Warchulska, Katarzyna; Lizińczyk, Sebastian (Frontiers in Psychiatry, 2021)
Lately, the question about potentially problematic characteristics of binge-watching has been raised in the recent literature. Binge-watching is a highly popular behaviour which is described as watching multiple episodes of TV series in one sitting. Studies show that binge-watching can be both entertaining and potentially problematic behaviour. The aim of this research is to answer the question how impulsivity, difficulties in emotional regulation and motivation to watch TV series predict the problematic binge-watching in the group of Polish young adults. The research group consists of 645 participants. The following methods were used in the study: Impulsive Behaviour Scale, Difficulties in Emotion Regulation Scale, Viewing Motivation Scale and Questionnaire of Excessive Binge-watching. The regression analysis was performed to answer research questions. The results of the research show that the lack of premeditation, impulse control difficulties and escape motivation are significant predictors of problematic binge-watching. Furthermore, motivation to deal with loneliness, motivation to spend free time, informative and entertaining motivations were also significant predictors of problematic binge-watching.